(untitled) (Conferencea, 2024)
As a result of the increasing competition for attracting financial institutions in the world, serious attention is paid to improving the invective environment in countries, their regions, relevant sectors of the economy and regions. Today, the "Foreign Direct Investment Flow" returned to pre-pandemic levels in 2022 and amounted to USD 1.6 trillion. At the same time, the scale of financing of cross-border transactions and international projects has been dramatically expanded. However, the recovery of the invective environment in developing countries remains fragile. The fragile socio-political situation that the world is currently facing is exacerbated by the COVID-19 pandemic, which is still ongoing, as well as climate change, which exacerbates the vulnerability in the invective environment." It will ensure the active attraction of invections to the regions, the improvement of financial mechanisms, the increase and improvement of the attractiveness of the invective environment, and the effective use of tax incentives.